The media relations of Universitas Ahmad Dahlan Yogyakarta in maintaining image during the COVID-19 Pandemic: (Case study of UAD media relations in 2021) - Pratiwi, Nadia; Anisa Sari, Eka (COMMICAST, 2023)
The COVID-19 pandemic in 2021 has affected the education in Indonesia, including the institution of Universitas Ahmad Dahlan (UAD) Yogyakarta.  The existence of educational institutions requires existence to gain the trust of the community. Public relations become an element that plays a role. During the COVID-19 pandemic, the use of media helps the public in obtaining and conveying information, including media coverage. Therefore, it is important for university public relations to have a good relationship with the media, considering that the media is a source of information providers. This study aims to determine the implementation of media relations carried out by UAD Public Relations in maintaining its image during the COVID-19 pandemic in 2021. The goal is to know and understand the implementation of media relations applied, starting from the research stage, preparation, communicating a program, and evaluations. This research method uses a qualitative with a case study approach and was analyzed using John E. Marston's R-A-C-E Formula. Based on data, at the research stage the implementation is not maximized, so that offline activities have no substitute activities. At the action stage, media relations activities include preparation of public relations writing skills, release materials, and advertising publication materials. Stages of communication conducting media relations activities, namely making press releases and advertising publications. In addition, to build a good relationship with the media, UAD Public Relations maintains personal contact with media partners, provides souvenirs, and Feast Day gifts.  Finally, at the evaluation stage, UAD Public Relations monitors publications and program evaluation.